Personality assessment in America : a retrospective on the occasion of the fiftieth anniversary of the Society for Personality Assessment /: a retrospective on the occasion of the fiftieth anniversary of the Society for Personality Assessment. (2019) - Megargee, Edwin Inglee; Spielberger, Charles Donald, 1927-2013
No abstract available